Proceedings of the 2014 ACM International Joint Conference on Pervasive and Ubiquitous Computing: Adjunct Publication 2014
DOI: 10.1145/2638728.2638811
|View full text |Cite
|
Sign up to set email alerts
|

Beyond sensors

Abstract: Mobile technology for remotely sensing key health indicators about patients receiving long-term or outpatient care continues to become more affordable and more easily embedded, but there remain certain patient variables, especially mental health and adaptive functioning characteristics, that are difficult to automatically detect or problematic to self-report. To address this problem, we are working on technology that integrates input from caregivers (as well as patients) with enhanced context reporting. We des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Studies of this type focus on the use of remote sensor and monitoring systems to track a person’s health activity and report it to a designated family member or caregiver [6,35]. Barish et al examined leveraging mobile sensors and input from the caregiver in the context of outpatients with mental health disorders [2]. Topo discussed the use of technology among at-home patients diagnosed with dementia and their caregivers, and acknowledged informal and formal caregivers as end users of technology to support their diverse needs, in addition to the ability for technology to improve caregiver wellbeing [32].…”
Section: Related Workmentioning
confidence: 99%
“…Studies of this type focus on the use of remote sensor and monitoring systems to track a person’s health activity and report it to a designated family member or caregiver [6,35]. Barish et al examined leveraging mobile sensors and input from the caregiver in the context of outpatients with mental health disorders [2]. Topo discussed the use of technology among at-home patients diagnosed with dementia and their caregivers, and acknowledged informal and formal caregivers as end users of technology to support their diverse needs, in addition to the ability for technology to improve caregiver wellbeing [32].…”
Section: Related Workmentioning
confidence: 99%
“…And, a lack of context can make data difficult to interpret, as Slovak et al [30] found in relation to the sharing of heart rate among couples, for example. Collaborations with personal informatics data has also been studied in chronic self-care applications [1,3,9,31,35,39]. While in some cases the analysis of data can be a joint effort in this domain [1,9], in contrast to our approach here the sharing (and importantly, making sense of) data is still unidirectional.…”
Section: Introductionmentioning
confidence: 99%